2012
DOI: 10.17584/rcch.2010v4i2.1242
|View full text |Cite
|
Sign up to set email alerts
|

Efecto inhibitorio de extractos de Swinglea glutinosa (Blanco) Merr. y Lantana camara L. en preemergencia y posemergencia.

Abstract: Cerca viva de Swinglea glutinosa en el eje cafetero (Colombia). Foto G. Fischer Para determinar el efecto inhibitorio de los extractos vegetales extraídos de las especies Swinglea glutinosa y Lantana camara se realizaron ensayos de preemergencia y posemergencia, con siete concentraciones (0; 0,5; 1,0; 1,5; 2,0; 3,0 y 5,0% v/v), a cinco especies de arvenses (Senna obtusifolia, Amaranthus dubius, Rumex crispus, Brassica rapa y Poligonum segetum) y cinco de cultivos comerciales (arroz, maíz, zanahoria, lechuga y … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 5 publications
0
4
0
2
Order By: Relevance
“…(Rutaceae) y Lantana camara L. (Verbenaceae) fue evaluado sobre semillas de diferentes arvenses. Los resultados mostraron que los extractos tienen potencial inhibitorio sobre la germinación de las especies evaluadas (Gil et al, 2012), lo que concuerda con los resultados obtenidos en el presente estudio.…”
Section: Resultados Y Discusión Fase 1 Germinacion De Semillasunclassified
“…(Rutaceae) y Lantana camara L. (Verbenaceae) fue evaluado sobre semillas de diferentes arvenses. Los resultados mostraron que los extractos tienen potencial inhibitorio sobre la germinación de las especies evaluadas (Gil et al, 2012), lo que concuerda con los resultados obtenidos en el presente estudio.…”
Section: Resultados Y Discusión Fase 1 Germinacion De Semillasunclassified
“…According to Jabran (2017), the chemical inhibitors contained in plant extracts produced by allelopathic agents correspond to secondary metabolites and belong to various classes of compounds such as phenols, aldehydes, glucosides, terpenes, and organic cyanogenic compounds. Gil et al (2010) reported that the application of the extracts of Swinglea glutinosa and Lantana camara inhibited the germination of Senna obtusifolia, Amaranthus dubius, Rumex crispus, Brassica rapa, and Poligonum segetum. In the case of Swinglea, the extracts inhibit germination with the concentration 0.5% and Lantana inhibits germination with an extract of 2.0% (Gil et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Gil et al (2010) reported that the application of the extracts of Swinglea glutinosa and Lantana camara inhibited the germination of Senna obtusifolia, Amaranthus dubius, Rumex crispus, Brassica rapa, and Poligonum segetum. In the case of Swinglea, the extracts inhibit germination with the concentration 0.5% and Lantana inhibits germination with an extract of 2.0% (Gil et al, 2010). Seabra et al (2017) evaluated allelopathic concentrations of Canavalia ensiformis on the seed germination of Carthamus tinctorius, where the inhibition was obtained with an extract concentration of 75% indicating that the extract of C. lineatifolia is very efficient because it needed only 3% to inhibit germination.…”
Section: Resultsmentioning
confidence: 99%
“…and Parietaria judaica L. Its activity differed according to arvense on which acted: completely inhibited germination of A. hybridus, and controlled almost completely the germination of C. canadensis and P. judaica all concentrations tested, with no differences between them. Gil et al 16 determined the inhibitory effect of plant extracts of the species Swinglia glutinosa and Lantana camara, performing tests pre-emergence and post-emergence. In pre-emergence tests it found that S. glutinosa extract inhibited germination and root length decreased weeds when seed was applied with the lowest concentration (0.5%).…”
Section: Verdaguermentioning
confidence: 99%